Identification of bioactive metabolites in Turnera ulmifolia: Preliminary phytochemical screening and FTIR analysis - Monica, S; Manikantan, P (Plant Science Today, 2025)
Turnera ulmifolia L., a member of the Passifloraceae family, is widely distributed across tropical and subtropical regions. Though frequently considered a weed, it has been commonly used in folk medicine to treat inflammation, infections, wounds and digestive ailments. Earlier studies have found alkaloids, flavonoids, tannins, terpenoids and polyphenols in species from the same genera that contribute to their therapeutic efficacy. Despite its ethnomedicinal value, the phytochemical profile and functional group characterization of T. ulmifolia are still unexplored. This study aimed to investigate the phytochemical composition of its leaf, stem and root extracts using different solvents (methanol, ethanol, hexane and acetone) and identify key functional groups through FTIR analysis. Phytochemical screening confirmed the presence of diverse secondary metabolites. FTIR analysis further revealed functional groups such as O=C=O, C=C and S=O, which are associated with therapeutic properties. Notably, alkaloids were abundant in leaf extracts, while sulfoxide groups, known for their herbicidal and medicinal effects, were detected in the stem. These findings reinforce the pharmacological potential of T. ulmifolia as a promising source of bioactive metabolites with medicinal and ecological applications. Its capacity to diversify in various habitats and create bioactive molecules under stress points to possible uses in medicine discovery, sustainable agriculture and environmental restoration. This study lays the groundwork for future research to validate its therapeutic potential and explore its integration into modern pharmaceutical and ecological solutions.